Speech Acts Analysis In The Fantasy Movie “Godmothered” - Turnip, Gresy; Hutauruk, Bertaria Sohnata; Purba, Rudiarman (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2025)
Fantasy films often present imaginative storylines that explore the interpretation of magic in the real world. However, viewers frequently struggle to understand the meaning behind the characters' utterances and the actions resulting from these dialogues. This study analyzed the fantasy film Godmothered to explore how the use of magic in the real world generates actions through speech acts in the characters' dialogues. The aim of this study was to identify and analyze the different types of speech acts in the film, as well as their role in character development and thematic expression. Using (Yule, 2022) theory of speech acts, which categorizes speech acts into five types, this qualitative descriptive research focused on two main characters and analyzed their dialogues through the transcript of their conversations. The results revealed that three types of speech acts were most prominent in the film: representative acts (informing, stating, expressing opinions, rejecting, and confessing), expressive acts (requests, expressions of happiness, greetings, anger, offers, warnings, and apologies), and directive acts (requests, expressions of happiness, greetings, anger, offers, warnings, and apologies). This study highlights the significance of speech acts in understanding character dynamics and the thematic structure of fantasy films.